Anemonoides × lipsiensis comb. nov. (Ranunculaceae), new for the Italian flora - Giovanni Astuti; Giancarlo Marconi; Paolo Pupillo; Lorenzo Peruzzi (Italian Botanist, 2019)
The hybrid Anemonoides nemorosa × A. ranunculoides is recorded for the first time in Italy at the southern periphery of Bologna (N Italy, Emilia-Romagna). Its status is supported by both morphological features and chromosome number (2n = 31). For this taxon, a new nomenclatural combination is proposed.